Efecto del tiempo de almacenamiento en la viabilidad, germinación de semillas de maní (arachis hypogaea l) de la UTMACH - Ochoa Jaramillo, Richard Fernando (Machala : Universidad Técnica de Machala, 2018)
Peanuts (A. Hypogaea. L.) is a oilseed of great agricultural importance at the commercial level, in the country is a culture of little transcendence due to the lack of research and machinery for its harvest, it is a culture of family type, related to cultural customs, ancestral, that is used In the preparation of meals, candies and beverages. There is little information about the right way to manage the crop, especially how to keep your seeds for long periods without losing their viability and genetic vigor. Ecuador is center of origin of this species, therefore, there is a great diversity of peanuts with a great potential use in food and agro-industry, for its great nutritional value. This research was carried out at the Experimental Farm "Santa Inés" that belongs to the academic unit of Agricultural Sciences (UACA), of the Technical University of Machala (UTMACH), located in the parish El Cambio, Canton Machala. The objective of the work was: to check the effect caused by the time and the type of storage in the viability and germination of peanut seeds (A. Hypogaea L.). To carry out the experimental work, nine accessions of peanuts harvested and stored in different years were used (3 of 2016, 3 2017 and three 2018) belonging to the Germplasm Bank (UACA). To evaluate the germination power of the seeds, germination test was carried out in substrate (organic matter), this evaluation did not provide results, due to the low germination of the seeds (2016 and 2017 stored). Before this, a test of germination was proposed in laboratory, following the norms of the ISTA, but it was also used as a means of germination biocoal ground. The data obtained in the laboratory and field tests were submitted to the statistical analysis by means of a Anova and Tukey's tests at 0.05 using the statistical Package for the Social Sciences (SPSS) program. The dependent variables assessed were: Percentage of germination and establishment in field (days to flowering, number of branches to flowering, leaves to flowering and plant height to flowering). The results showed that germination in substrate was not given in accessions that have been stored more than 1 year, storage time if it influenced this process. In the laboratory test using biochar as a means of germination, there is no significant difference between the peanut accessions according to the storage time with germination, the storage time did not influence. The seeds of TC2018 that contain more moisture, presented a lower rate of germination capacity, the seeds of TC2016 and TC2017 that contain less moisture, but showed a high degree of germination. In the establishment in the field, the best vigor of peanut plants was obtained, of the TC2018 group, instead, TC2016 was the group that presented the least morphological development. The results show that the moisture content at the time of storage and maintain the seeds contained in its natural capsule influence its viability, establishment in field and genetic vigor.
El maní (A. hypogaea. L.) es una oleaginosa de gran importancia agrícola a nivel comercial, en el país es un cultivo de poca trascendencia por la falta de investigación y maquinarias para su cosecha, es un cultivo de tipo familiar, relacionado a costumbres culturales, ancestrales, que es usado en la preparación de comidas, dulces y bebidas. Existe escasa información sobre la forma correcta de manejar el cultivo, y en especial cómo conservar sus semillas por largos periodos sin que estas pierdan su viabilidad y vigor genético. Ecuador es centro de origen de esta especie, por lo tanto, existe una gran diversidad de maníes con un gran potencial uso en la alimentación y en la agroindustria, por su gran valor nutricional. Esta investigación se realizó en la Granja Experimental “Santa Inés” que pertenece a la Unidad Académica de Ciencias Agropecuarias (UACA), de la Universidad Técnica de Machala (UTMACH), ubicada en la Parroquia El Cambio, cantón Machala. EL objetivo del trabajo fue: comprobar el efecto provocado por el tiempo y el tipo de almacenamiento en la viabilidad y germinación de semillas de maní (A. hypogaea L.). Para realizar el trabajo experimental se utilizaron nueve accesiones de maní cosechadas y almacenadas en años diferentes (3 de 2016, 3 2017 y tres 2018) pertenecientes al Banco de Germoplasma (UACA). Para evaluar el poder germinativo de las semillas, se realizó prueba de germinación en sustrato (materia orgánica), esta evaluación no proporcionó resultados, por la baja germinación de las semillas (2016 y 2017 almacenadas). Ante esto, se propuso una prueba de germinación en laboratorio, siguiendo las normas del ISTA, pero además se utilizó como medio de germinación biocarbón molido. Los datos obtenidos en los ensayos de laboratorio y de campo fueron sometidos al análisis estadístico mediante un Anova y pruebas de Tukey al 0.05 usando el programa Statistical Package for the Social Sciences (SPSS). Las variables dependientes evaluadas fueron: porcentaje de germinación y establecimiento en campo (días a la floración, número de ramas a la floración, hojas a la floración y altura de planta a la floración). De los resultados obtenidos se evidenció que, la germinación en sustrato no se dio en accesiones que han estado almacenadas más de 1 año, el tiempo de almacenamiento si influyó en este proceso. En la prueba de laboratorio utilizando biocarbón como medio de germinación, no existe diferencia significativa entre las accesiones de maní de acuerdo al tiempo de almacenamiento con la germinación, el tiempo de almacenamiento no influyó. Las semillas de TC2018 que contienen mayor humedad, presentaron un índice menor de capacidad de germinación, las semillas de TC2016 y TC2017 que contienen menos humedad, pero mostraron un alto grado de germinación. En el establecimiento en campo, se obtuvo el mejor vigor de plantas de maní, del grupo TC2018, en cambio, TC2016 fue el grupo que presentó el menor desarrollo morfológico. Los resultados demuestran que el contenido de humedad al momento del almacenamiento y mantener las semillas contenidas en su cápsula natural influyen en su viabilidad, establecimiento en campo y vigor genético.
Keywords: OLEAGINOSA; CULTIVARES; BIOCARBÓN; VIGOR